Agrobiodiversity and associated trophic interactions as an indicator of sustainability in 73 productive systems of Argentine Pampeana Region - Taraborelli, Paula Andrea; Carrasco, Natalia; Malaspina, Micaela; Domínguez, Cecilia; Scavone, Andrea Soledad; Zamora, Martin Sergio (Universidad de Murcia; Sociedad Española de Agricultura Ecológica, 2025)
Biodiversity is crucial in agroecosystems, as it makes them more efficient, stronger, productive and resilient. The aim was to determine and compare the existing biodiversity in two different production systems: agroecological and industrial during 2018 and 2019 in the INTA Barrow (Buenos Aires, Argentina). Sampling of mammals, birds, arthropods and spontaneous vegetation were made in wheat and oat crops. Several parameters were estimated including abundance, density, richness, dominance, diversity and equitivity for each study group. The agroecological system presented higher density of birds and mammals, richness of arthropods and spontaneous species compared to the industrial system. The greater agricultural diversification in the agroecological system evidenced a more complex landscape structure, through the increase in the richness of spontaneous species and beneficial fauna that would increase the potential for biotic regulation of the system.